Threshold dose response for tumor induction by genotoxic carcinogens modeled via cell-cycle delay - Lutz, Werner; Kopp-Schneider, Annette (Toxicological sciences, 1999)
Abstract. Dose-response relationships for tumor induction in animal bioassays for carcinogenicity are often postulated to include thresholds, particularly for
Gesehen am 19.10.2020